(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this article, the impact of social and political processes in ancient times on people’s lifestyle, the role of specific culture in the development of types are analyzed. In particular, the influence of sociopolitical processes on the formation of the “Kovunchi” culture in Ancient Ustrushona is discussed